Mapping the Demotic Epistolary Framework through Network Visualisation - Dogaer, Nico (Zeitschrift für ägyptische Sprache und Altertumskunde, 2017)
In this article, network visualisation is presented as a new way to explore the formulaic framework of the Demotic papyrus letters. It also serves as an introduction of formal network analysis to the field of Demotic studies. This approach presents the evidence in a new light, focussing on the combination of formulae rather than on the phrases themselves, resulting in fresh observations on epistolary practices.